A Nanoindentation Device and the Scale-Dependent Mechanical Properties of Native and Decellularized Liver Tissue - Evans, Douglas W (Wake Forest University, 2011)
Regenerative medicine is an emerging field with the goal of treating disease with engineered replacements for cells, tissues, and organs. One technique in regenerative medicine is decellularization, the removal of the native cells from an organ leaving behind an intact structure of extracellular material to act as a scaffold for new cells. Characterizing the biomechanical properties of these scaffolds is important due to the mechanosensitivity of many cell types. In addition, in the emerging field of multi-scale modeling an effort is being made to integrate the small fundamental scales with the large functional scales that exist in the hierarchial structure of biological systems. The aim of this work was to investigate and quantify the biomechanical properties of perfused decellularized liver scaffolds and compare them to perfused native tissue properties on both a macro and nano-scale. To accomplish this goal, a novel Nano-Tissue Indenter (NTI) was constructed that can be used to perform nanoindentation on virtually any soft biologic tissue or biomaterial. The device was validated by comparing its measurements with results obtained through traditional unconfined compression testing. The NTI was used along with conventional macro-indentation to evaluate mechanical property differences in native and decellularized liver at the tissue and cellular-scales. A poroviscoelastic (PVE) finite element model was employed to capture the solid and fluid components of liver material behavior. The end result of this work was the first characterization of the biomechanical properties of perfused decellularized liver tissue and how it differs from perfused native tissue measured by spherical macro and nanoindentation.
Keywords: decellularized liver; Extracellular Matrix; Liver; Multiscale modeling; Nanoindentation; poroviscoelastic